Ensino religioso escolar: ponderações sobre aspectos dialógicos e epistemológicos - Melo, Arthur Felipe Moreira de (2014)
This paper examines possible epistemological contributions to the teaching practice of Religious Education in public schools, prioritizing the teacher as the main interlocutor. The dissertation is divided into three chapters. The first is devoted to the history of Religious Education in Brazil and has rather a political approach. It attempts to cover the history of Religious Education in Brazil from the colonial period to the present day, pointing to some of the most current querries on the subject. The second chapter discusses the epistemological querry of Religious Education from an interface between phenomenology and language. Some of the presuppositons related to the Religious Education teaching practice are addressed as well as the threshold and depth dimensions in the treatment of religious phenomena. This chapter also includes an analysis of some contributions offered by the cross-culture studies to the Religious Education. The third and last chapter analyzes some epistemological reflections on the teaching praxis of Religious Education. Some subjects are analyzed, like the language used in Religious Education supporting literature, the approach to the semantic universe of different religious traditions that are represented in the classroom, general conditions of cross-religious dialogue in the classroom, the issue of skepticism in Religious Education class, and, finally, the approach to the phenomenon of syncretism.